A Comparative Study on Fatigue Damage using a Wave Load Sequence Model - De Gracia, Luis; Osawa, Naoki; Tamaru, Hitoi; Fukasawa, Toichi (KnE Engineering, 2018)
Despite that ships get the approval of classification societies and structural members are designed to survive random environmental conditions for twenty or twenty-five years, fatigue crack damage still occurs. Nowadays, the operation based on weather routing programs has become important, not only to avoid adverse sea conditions that can cause damage, time loss or significant speed reduction but also to improve the crew safety. In this paper, S-N based fatigue assessment of a welded joint in an ocean going is performed. It is assumed that the ship sails following a planned route and a route based on weather conditions. Short sea sequences are generated by a storm model called “4G Storm Model”, proposed by one of the co-authors (De Gracia et al., 2017). Stress histories are generated considering the stochastical nature of the wave direction variation. Cumulative fatigue damage is performed following a classification society rule. Based on these results, the effect of ship routing and headings model on the S-N fatigue assessment is discussed. Keywords: Weather routing, fatigue, cumulative damage, storm model, wave sequence model.